AB0191 Clinical significance of multiple autoantibody specificities in rheumatoid arthritis: the role of anti-citrullinated alpha enolase and anti-interferon inducible protein 16. (15th June 2017) - Alunno, A; Bistoni, O; Pratesi, F; Caneparo, V; Paglia, GMC La; Puxeddu, I; Andrea, M De; Bartoloni, E; Landolfo, S; Migliorini, P; Gerli, R
Abstract : Background: Anti-cyclic citrullinated peptide (anti-CCP) auto-antibodies (auto-Abs) represent the current gold standard for the diagnosis of rheumatoid arthritis (RA). However, growing evidence suggests that a variety of other citrullinated or not citrullinated self-proteins may act as autoantigens and lead to the production of auto-Abs. The identification of the diagnostic and/or prognostic value of such novel auto-Abs is under intense investigation. We recently demonstrated that RA patients display a higher prevalence of auto-Abs against the interferon-inducible protein 16 (anti-IFI16) but these auto-Abs do not have a good diagnostic value (1). Recent data showed that auto-Abs against citrullinated alpha-enolase (anti-CEP1) are associated with erosive RA (2). Objectives: The purpose of this study was to investigate the possible prognostic value of anti-CEP-1 and anti-IFI16 as well as the clinical implication of their association with anti-CCP in a cohort or RA patients. Methods: Two hundred and fifty two RA patients were enrolled and serum samples were obtained. Auto-Abs were assessed as follows: anti-CCP EDIA 2nd generation ELISA kit (Eurodiagnostica); anti-CEP-1 IgG ELISA kit (Euroimmun). In a subgroup of 113 patients also anti-IFI16 auto-Abs were assessed with an in-house ELISA kit (1). Clinical and serological records of patients were collected and statistical analysis was performed with SPSS 21.0 software. Results: One hundred and twenty patients (44%) displayed anti-CEP-1 auto-Abs and of these 97 patients (87%) also displayed anti-CCP. Logistic regression analysis revealed an association between both auto-Abs and RA-associated pulmonary disease (odds ratio-OR=2.9; 95% CI=1.06–7.9; p=0.04). We also confirmed that anti-CEP-1 are associated with erosive RA but of interest to a greater extent compared to anti-CCP (anti-CEP-1: OR=4.12; p=0.04; anti-CCP: OR=2.1; p=0.03). The analysis that included anti-IFI16 auto-Abs revealed that a small proportion of patients display all the three auto-Abs (9%) but the triple positivity was significantly associated with male gender (OR=3.5; p=0.02), the presence of rheumatoid nodules (OR=5, 3; p=0.015) and pulmonary involvement (OR=2.6; p=0.007). Anti-IFI16 auto-Abs were associated to male gender independently of the presence of the other two auto-Abs. Conclusions: Our study demonstrated that anti-CEP-1 auto-Abs may participate to the development of RA-associated pulmonary manifestation together with anti-CCP and that the assessment of multiple auto-Abs in daily practice may help clinician to stratify RA patients at identify those at higher risk to develop extra-articular manifestations. References: Alunno A et al. Arthritis Care Res (Hoboken) 2016;68(4):440–5. Montes A et al. Arthritis Rheum 2012;64(10):3102–3110. Disclosure of Interest: None declared